The spatial evolution of the chemotaxis proteins of the Bacillus subtilis group - Yssel, Anna Elizabeth Johanna (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2011)
The aim of this work was to study spatial evolution of the chemotaxis proteins of a group of plant-associated soil-dwelling bacteria vernacularly referred to as the B. subtilis group. This was achieved by creating homology models for the chemotaxis proteins if a suitable template was available, and by analysing the selective forces (positive, purifying or neutral) acting upon the chemotaxis proteins. Chemotaxis is the phenomenon in which bacteria direct their movement towards more favourable conditions, and is critical for processes such as obtaining nutrients, escaping toxic compounds, host colonization and bio-film formation. Members of the B. subtilis group exhibit different preferences for certain host plants, and it is therefore feasible that their chemotactic machinery are fine-tuned to respond optimally to the conditions of the various niches that the strains inhabit. Homology models were inferred for the plant growth promoting B. amyloliquefaciens FZB42 proteins CheB, CheC, CheD, CheR, CheW and CheY. The interactions between: CheC-CheD, the P1 and P2 domains of CheA with CheY and CheB, and the P4 and P5 domains of CheA with CheW were also modelled. The hydrophobic interactions contributing to intra- and inter-protein contacts were analysed. The models of the interactions between CheB and the various domains of CheA are of particular interest, because to date no structures have been solved that show an interaction between a histidine kinase (such as CheA) and a multidomain response regulator (such as CheB). Furthermore, evidence that phospho-CheB may inhibit the formation of phospho-CheY by competitively binding to the P2 domain of CheA is also presented. Proteins were analysed to determine if individual amino acid sites are under positive, neutral or purifying selection. The Methyl Accepting Chemotaxis Proteins (MCPs), CheA and CheV were also analyzed, but due to a lack of suitable templates, no homology models were constructed. Site-specific positive and purifying selection were estimated by comparing the ratios of non-synonymous to synonymous substitutions at each site in the sequences for the chemotaxis proteins as well as for the receptors McpA, McpB, and McpC. Homology models were coloured according to intensity of selective forces. It was found that the chemotaxis proteins of member of the B. subtilis group are under strong evolutionary constraints, hence it is unlikely that positive selection in these proteins are responsible for the differences in habitat preference that these organism exhibit.
Keywords: Chemotaxis; Bacillus subtilis; Bacillus (Bacteria); Homology (Biology); Plants -- Microbiology